A legal look at the Arias case and double conformity. Comments on Judgment SU-146 of 2020 of the Constitutional Court (2020)
The Sentence SU146 of 2020, by which the court decided to order the Criminal Cassation Chamber of the Supreme Court of Justice to initiate “the process to resolve the request to challenge the sentence in sole instance issued against citizen Andrés Felipe Arias Leiva” is a current political discussion. This is why it is taken as the object of analysis to make respective comments, in addition, to relate to this the principle of conformity and its evolution in the order.